2002
DOI: 10.1002/pros.10088
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of vimentin in motile prostate cell lines and in poorly differentiated and metastatic prostate carcinoma

Abstract: Motile prostate cancer cell lines express vimentin. In tissue sections, the presence of vimentin positive tumour cells correlated positively to poorly differentiated cancers and the presence of bone metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
94
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 30 publications
19
94
1
3
Order By: Relevance
“…Vimentin is a characteristic marker for the mesenchymal phenotype of cancer cells, and enhanced vimentin expression was previously found in motile prostate cell lines and in poorly differentiated and metastatic prostate carcinoma. 41 In line with these observations, we found that vimentin expression increased with tumorigenicity and that E-cadherin/vimentin ratios decreased with augmented invasiveness and aggressiveness (Figure 2a). BMP7 mRNA levels in prostate cancer cell lines strongly correlated to E-cadherin/vimentin ratio (Figure 2, a and b), whereas no association was observed for other BMPs (results not shown).…”
Section: Bmp7 Mrna Expression In Prostate Cancer Cell Linessupporting
confidence: 84%
“…Vimentin is a characteristic marker for the mesenchymal phenotype of cancer cells, and enhanced vimentin expression was previously found in motile prostate cell lines and in poorly differentiated and metastatic prostate carcinoma. 41 In line with these observations, we found that vimentin expression increased with tumorigenicity and that E-cadherin/vimentin ratios decreased with augmented invasiveness and aggressiveness (Figure 2a). BMP7 mRNA levels in prostate cancer cell lines strongly correlated to E-cadherin/vimentin ratio (Figure 2, a and b), whereas no association was observed for other BMPs (results not shown).…”
Section: Bmp7 Mrna Expression In Prostate Cancer Cell Linessupporting
confidence: 84%
“…Importantly, the retargeted virus demonstrated no transduction above that of pc-Adluc, in the cells derived from normal prostate epithelia suggesting that the risk of inappropriate transgene expression in healthy tissue would be low. Although we detected b1 integrin subunits on both PNT1a and PNT2 cells in agreement with previous studies, 50,51 we would expect these cells to maintain b4 integrin subunit expression to which the a6 subunit would preferentially dimerize, SIKVAV being unable to bind integrin a6b4. 52 Summary of flow cytometric analysis using specific monoclonal anti-a6-integrin subunit and monoclonal anti-b1-integrin subunit antibodies on a panel of human cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…S7). Our results demonstrate that tumors driven by NICD1 in combination with kRas G12D , myrAKT, and Myc exhibit EMT features, a phenotype that may characterize invasive, poorly differentiated carcinoma (42)(43)(44)(45).…”
Section: Gene-expression Profiling Of Tumors Driven By Nicd1 In Combimentioning
confidence: 65%